Patient‐reported outcomes in human papillomavirus‐related oropharyngeal cancer. Issue 6 (2nd October 2021) - Fitzgerald, Conall W. R.; Long, Sallie M.; McLean, Andrew T.; Cracchiolo, Jennifer R.
Abstract: This review explores how human papillomavirus‐related oropharyngeal cancer affects health‐related quality of life (HR‐QoL) and the role patient‐reported outcomes (PROs) can play in optimizing treatment. PRO measures (PROMs) are comprehensive, subjective assessments of patients' day‐to‐day HR‐QoL. Developed through a scientifically robust, multistage process, PROMs offer insight into patients' symptoms, function, and satisfaction with care. The use of PROMs can increase symptom awareness, stimulate discussion, and enhance shared decision‐making between patients and healthcare providers.